The Creative Perpetuation in Didactic Literature Influenced by Ramayana of Phra Dharmasastra (Suk) - darunaitorn, artid; Prommas, Chanika; Nakthaen, Kamollada (Fa Nuea Journal, 2022)
Phali Son Nong and Phipek Son Benyakai are didactic literatures of Phra Dharmasastra (Suk), the poet in the reign of King Rama V. The author brought the characters and the content from the Ramayana to be the teaching strategies. The poetic verse: Phali Son Nong which originated from the episode before Phali died from the arrow of Brahma. The Brahma disciplined Sugriva, Angada, and Hanuman one last time to realize the discipline of working as bureaucrat. For the poetic verse: Phipek Sorn Benyakai originated from the episode where Ravana exiled Phipek out of Krung Long Ka. He came to say farewell to Sarama (his wife) and Benyakai (his daughter) and taught Benyakai how to behave as a proper lady. Though bringing the characters and the content from Ramayana to be a didactic literature is not new, the poetic verse of Phali Son Nong and Phipek Son Benyakai of Phra Dharmasastra (Suk) are very interesting in terms of the creative strategy by choosing the characters and the opportunities to teach both related and different from the traditional norm. Moreover, the author focused on the creation of emotional feeling towards the readers by various literary strategies such as the introduction to the characters, the setting of dramatization, and the use of lamented verses which were different from the other didactic literatures influenced by Ramayana in the past that only emphasized on the diction in didacticism.